2006
DOI: 10.1089/cpb.2006.9.584
|View full text |Cite
|
Sign up to set email alerts
|

Friend Networking Sites and Their Relationship to Adolescents' Well-Being and Social Self-Esteem

Abstract: The aim of this study was to investigate the consequences of friend networking sites (e.g., Friendster, MySpace) for adolescents' self-esteem and well-being. We conducted a survey among 881 adolescents (10-19-year-olds) who had an online profile on a Dutch friend networking site. Using structural equation modeling, we found that the frequency with which adolescents used the site had an indirect effect on their social self-esteem and well-being. The use of the friend networking site stimulated the number of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
770
5
36

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,198 publications
(853 citation statements)
references
References 10 publications
42
770
5
36
Order By: Relevance
“…For example, a longitudinal follow-up to the original HomeNet study found no long-term effects of Internet use on loneliness or depression (Kraut et al, 2002). Valkenburg, Peter, and Schouten (2006) note a major shortcoming of previous Internet research. Many of the studies treat Internet use as a one-dimensional activity.…”
Section: Does Participation In Sns Affect Psychological Well-being Anmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a longitudinal follow-up to the original HomeNet study found no long-term effects of Internet use on loneliness or depression (Kraut et al, 2002). Valkenburg, Peter, and Schouten (2006) note a major shortcoming of previous Internet research. Many of the studies treat Internet use as a one-dimensional activity.…”
Section: Does Participation In Sns Affect Psychological Well-being Anmentioning
confidence: 99%
“…For example, Valkenburg et al (2006) find that within a sample of over 800 Dutch adolescents, SNS use is related to self-esteem and psychological well-being. Adolescents who frequently use an SNS have more friends on the site and also more reactions on their profile (i.e., friends posted more comments and wall posts).…”
Section: Does Participation In Sns Affect Psychological Well-being Anmentioning
confidence: 99%
“…Social media, however, is a very large component that today's adolescents occupy. It has been shown that social media sites such as Facebook, also provide positive experiences for adolescents including greater access to social resources and enhanced social connections and learning (Valkenburg, Jochen, & Schouten, 2006). In the current study the reflexive role of the facilitator was therefore to hold open any prior judgement of the experiences of adolescents so as truly hear the complex and sometimes nuanced perspectives and experiences of these adolescents with social media.…”
Section: Statement Of Reflexivitymentioning
confidence: 99%
“…Furthermore, some researchers have been able to carry out the first longitudinal analyses in the field (see for example Steinfield et al 2008). According to this strand of the literature, SNSs support the strengthening of bonding and bridging social capital (Valkenburg et al 2006, Steinfield et al 2008, Gilbert et al 2009, Burke et al 2009), allow the crystallization of weak or latent ties that might otherwise remain ephemeral (Haythornthwaite 2005, support teenagers' self-esteem -encouraging them to relate to their peers , Steinfield et al 2008, stimulate social learning (Burke et al 2010), enhance social trust, civic participation and political engagement (Valenzuela et al 2009), facilitate the creation of electronic networks of practice (Vasko and Faray 2005, Landqvist and Teigland 2010, Matzat 2010, and help the promotion of collective actions to the pursuit of shared goals (Landqvist and Teigland 2010). Drawing on survey data from a random sample of 800 Michigan State University undergraduate students, Ellison et al (2007) find that certain kinds of Facebook use can help students accumulate and maintain bridging social capital.…”
Section: Related Literaturementioning
confidence: 99%